Lola out loud : inspired by the childhood of activist Dolores Huerta - Torres, Jennifer, 1980- (Little, Brown and Company, 2022)
As Lola helps her mother at the family's hotel, she learns about compassion, social injustice, and how one voice can lead to change. Includes author's note on Dolores Huerta, a labor organizer who co-founded the National Farm Workers Association.